Transnational Sex Workers in Malaysia: Methodological Challenges in Data Collection - Suppiah, Puspalata C.; Kaur, Surinderpal (Journal of Modern Languages, 2018)
Sex workers represent a community subject to constant stigmatisation and discrimination yet provide an excellent source of data for research about sex work. As part of a larger project on the discursive representations of sex workers in Malaysia, in this article we examine some methodological constraints associated with researching the vulnerable and hard-to-reach population of female transnational sex workers in Malaysia. We discuss the problems in gaining access to these workers, establishing trust and rapport with them, and confronting language barriers. The data for this research were obtained from interviews conducted with 15 sex workers from India, Indonesia, Myanmar, Thailand, and Vietnam. The interviews were conducted at a national shelter for rescued sex workers and in the field. By describing the methodological constraints that we encountered during data collection, we hope to expose some of the obstacles in the hope that doing so will benefit ethnographic researchers working with transnational sex workers.